Formación del Profesorado y Desarrollo Profesional en los Estados Unidos - Dossey, John (2011)
Those involved in mathematics education from kindergarten to eleventh year, have a very important and influential role in the development of society. They are the teachers who must train students in this area.However, some of the teaching staff training in mathematics, are not adequately prepared to do so, mainly teachers as the most basic levels from kindergarten to primary school.Aware of the need for training and in-service teacher training, is that some organizations of the United States have worked so hard to diagnose the magnitude of the problem and pose possible solutions within their nation.